2016
DOI: 10.1158/1078-0432.ccr-15-0534
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Activation Predicts Poor Outcome and the MEK Inhibitor, Selumetinib, Reverses Antiestrogen Resistance in ER-Positive High-Grade Serous Ovarian Cancer

Abstract: OBJECTIVE While 67% of high grade serous ovarian cancers (HGSOC) express the estrogen receptor (ER), most fail antiestrogen therapy. Since mitogen-activated protein kinases (MAPK) activation is frequent in ovarian cancer, we investigated if estrogen regulates MAPK and if MEK inhibition (MEKi) reverses anti-estrogen resistance. METHODS Effects of MEKi (selumetinib), anti-estrogen (fulvestrant), or both were assayed in ER+ HGSOC in vitro and in xenografts. Response biomarkers were investigated by gene expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 58 publications
4
71
0
Order By: Relevance
“…Despite a lack of mutations activating KRAS or BRAF in HGSOCs, we observed high levels of MEK1/2-ERK1/2 activity in a majority of clinical samples and cell lines. This observation is further supported by recently published studies reporting an association between high MAPK activity in HGSOC and poor survival [39,51]. Moreover, cisplatin treatment of HGSOC cells results in further MEK1/2 pathway activation that persists in cisplatin-resistant cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Despite a lack of mutations activating KRAS or BRAF in HGSOCs, we observed high levels of MEK1/2-ERK1/2 activity in a majority of clinical samples and cell lines. This observation is further supported by recently published studies reporting an association between high MAPK activity in HGSOC and poor survival [39,51]. Moreover, cisplatin treatment of HGSOC cells results in further MEK1/2 pathway activation that persists in cisplatin-resistant cells.…”
Section: Discussionsupporting
confidence: 77%
“…The function of the MEK1/2-ERK1/2 pathway has been mainly studied in low-grade ovarian tumors due to high frequency of activating KRAS and BRAF mutations [37,38]. Despite the absence of KRAS/BRAF mutations in HGSOC, MEK1/2 signaling hyperactivation was reported in HGSOC and is associated with poor prognosis [39]. The present paper aims to investigate the role of high MEK1/2 activity in the regulation of proliferation, viability, and stemness of HGSOC cells.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal activation of ERK1/2 pathway facilitates tumorigenesis, whereas, the stress-induced activation of JNK and p38MAPK controls the balance of cell autophagy and apoptosis [37, 38]. In this study, we observed that hnRNP-L upregulated p-ERK, p-p38 and p-JNK suggesting that hnRNP-L regulated cell fate in bladder cancer cells by promoting the MAPK (ERK/JNK/p38MAPK) signaling pathway.…”
Section: Discussionmentioning
confidence: 62%
“…RAS mutations are rare in BRCA1/2 mutated ovarian and breast cancers, but physiological pathway activation (6, 7) could mediate PARPi resistance, which could potentially be reversed by MEKi. In contrast, in other lineages such as pancreas and stomach, BRCA1/2 and KRAS mutations do co-occur (cBIOportal.org).…”
Section: Discussionmentioning
confidence: 99%